Growth, Mortality and Exploitation Rate of Pagellus bellottii Harvested from the Marine Territorial Waters of Sierra Leone - Konoyima, Komba Jossie; Seisay, Lahai Duramany (Acta Aquatica: Aquatic Sciences Journal, 2021)
The study investigated growth, mortality and exploitation rate of Pagellus bellottii collected off Sierra Leone, aimed to support efficient management of its stock.  A total of 8, 216 specimens of Pagellus bellottii were collected at random from January-November, 2016 on-board a demersal trawler. Data analysis employed methods implemented in the computerized FiSAT II software using pooled length-frequencies in constant class size. Growth parameters gave asymptotic length (Lˆž = 33.63cm), growth rate (K = 0.63yr-1), growth performance index (É¸ = 2.85), theoretical age (to = -0.6years) and life-span (tmax = 5.50years) whereas the length (Lm50) and age (tm50) at first maturity were estimated as 22.40 cm and 2.30years respectively. Besides, the current fishing mortality rate (F = 6.58yr-1) exceeded the optimum (Fopt = 0.50yr-1), limiting (Flimit = 0.81yr-1) and natural (M = 1.22yr-1) mortality rates, and the current exploitation rate (Ecurrent) was 0.84yr-1. Results depicted low life expectancy, fast growth and late first maturity (Lm50 = 33.4%, but < Lˆž) in Pagellus bellottii. Also, the stock of P. bellottii was overexploited (Ecurrent > 0.5), buttressed by the alarming current fishing mortality beyond optimal and permissible limits. This was very worrisome and the current exploitation rate should be reduced to 0.5yr-1 (40.5%) and fishing mortality rate to 0.5yr-1 (92.4%) in order to achieve at least optimal level of exploitation (Ecurrent = 0.5) and fishing mortality rate (Fcurrent = Fopt) respectively, through institution of closed fishing seasons and reduction in fleets targeting the species.Keywords: Exploitation; growth;  life-span; mortality; stock